KONSEP DESAIN BANGKU DAN KURSI SEKOLAH DASAR DI SURABAYA - Martadi, Martadi (Dimensi Interior, 2006)
This study is meant to explain thoroughly the underlying concept of desk and chair design for elementary schools in Surabaya, and to propose an alternative design concept which may be ideal for elementary school pupils. This study finds out that the design concept of desks and chairs for elementary school is very much affected by three educational matters, namely: the learning pattern that tends to be teacher-centered, too many pupils per classroom, and the school's financial capabilities. These three matters have given impacts on the design concept of desks and chairs which tends to be conventional with such a traditionally-patterned classroom arrangement. The factors being considered during the process of designing the desks and chairs for elementary schools are closely related with their natural and social-cultural environments, aesthetics, economy, function, and techniques. Those factors have significant impacts on the visual elements of those desks and chairs which can clearly be seen from their materials, constructions, measurements, shapes, and colors. Abstract in Bahasa Indonesia : Kajian ini bertujuan menjelaskan secara menyeluruh konsep pemikiran yang mendasari perancangan bangku dan kursi sekolah dasar khususnya di Surabaya dan merumuskan alternatif konsep perancangan bangku dan kursi sekolah dasar yang ideal. Hasil kajian memperlihatkan bahwa konsep perancangan bangku dan kursi sekolah dasar sangat dipengaruhi oleh tiga persoalan pendidikan yaitu pembelajaran yang cenderung berpola teacher-centered, besarnya jumlah siswa per kelas, dan kemampuan finansial sekolah. Ketiga persoalan tersebut berdampak terhadap konsep desain bangku dan kursi yang cenderung konvensional dengan pola ancangan ruang kelas tradisional. Faktor-faktor yang menjadi pertimbangan dalam proses perancangan desain bangku dan kursi sekolah dasar, berkaitan dengan lingkungan alam dan sosial budaya, estetis, ekonomi, fungsi maupun teknik. Faktor-faktor tersebut secara signifikan berpengaruh terhadap unsur visual bangku dan kursi, terlihat dari aspek material, konstruksi, ukuran, bentuk, dan warna. Kata kunci: desain, bangku dan kursi, sekolah dasar.